Wettability behavior of nanotubular TiO2 intended for biomedical applications - Rosa, Jorge Luiz; Nakazato, Roberto Zenhei; Scheneider, Sandra Giacomini; Alves Claro, Ana Paula Rosifini; Alves Rezende, Maria Cristina Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2014)
Nanotubes have been subject of studies with regard to their ability to promote differentiation of several cells lines. Nanotube have been used to increase the roughness of the implant surfaces and to improve bone tissue integration on dental implant. In this study TiO2nanotube layer prepared by anodic oxidation was evaluated. Nanotube formation was carried out using Glycerol-H2O DI(50-50 v/v)+NH4F(0,5 a 1,5% and 10-30V) for 1-3 hours at 37ºC. After nanostructure formation the topography of surface was observed using field-emission-scanning-microscope (FE-SEM). Contact angle was evaluated on the anodized and non-anodized surfaces using a water contact angle goniometer in sessile drop mode with 5 μL drops. In the case of nanotube formation and no treatment surface were presented 39,1° and 75,9°, respectively. The contact angle describing the wettability of the surface is enhanced, more hydrophilic, on the nanotube surfaces, which can be advantageous for enhancing protein adsorption and cell adhesion. Descriptors: Titanium; Nanotubes; Wettability.